PENGARUH PROMOSI PENJUALAN TERHADAP KECENDERUNGAN PEMBELIAN IMPULSIF PADA GERAI ALFAMART DI KECAMATAN MATUARI - Taliupan, Ratna (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Good economic growth is one of the factors that shows the development of a nation in a more advanced direction and the better the level of consumption of society when the era of globalization and modernization is moving towards a period of digitalization which results in every community need being met with various existing facilities and applications. Retail or retail business in Indonesia is one of the factors that can increase economic growth. Retail business consists of two types, namely traditional retail business and modern retail. In general, traditional retail actors are clontong stalls or small and medium enterprises, while modern retail is generally dominated by modern shops such as minimarkets and supermarkets, for example Alfamart, Indomaret, Alfamidi, Carefour and so on. The sample was taken based on the slovin formula with a total of 100 respondents. In analyzing the data, researchers used simple linear regression calculations, correlation coefficients, determination and hypothesis testing. From the results of the research, it was found that sales promotion has a significant influence on impulsive purchases at Alfamart outlets, receiving support in this study with a positive direction of influence. This significant influence is more directed to the value of sales promotions for products in daily needs for households.